MORFOMETRYC PERCENTAGE OF GIBLET MOJOSARI ALABIO DUCK THAT GIVEN SALAM LEAF EXTRAC (SYZIGIUM POLIANTUM) IN DRINKING WATER - Anggraeni, Anggraeni; Handarini, Ristika; Widiyantoro, Shena (Jurnal Peternakan Nusantara, 2019)
Mojosari x Alabio (MA) ducks have several advantages including higher egg productivity, early age of egg laying, faster growth, better production consistency, compared to its parents. The bay plant is scientifically named Latin Eugenia polyantha Wight. Bay leaves contain phenolic compounds, saponins, alkaloids, flavonoids and steroids. This study aims to determine the effect of giving bay leaf extract in drinking water on the percentage of giblet and mojosari alabio duck digestive apparatus. The research was carried out in the cages of the Animal Husbandry Study Program, Faculty of Agriculture, University of Djuanda, Bogor, from March to May 2019. The cattle used in this study were 100 mojosari alabio (MA) ducks aged 1 day which were kept until one week old (adaptation period). This study uses a completely randomized design (CRD) consisting of 5 replications and each repetition consists of 5 ducks. The treatments in this study consisted of 4 treatments: R0 = 0% bay leaf extract (control), R1 = 4% bay leaf extract, R2 = 8% bay leaf extract, R3 = 12% bay leaf extract. The data obtained were analyzed using the Analysis of variance (ANOVA), the results data were significantly different (P <0.05) followed by the Duncan test. The variables observed in this study were: giblet weight and digestive organ weight. The results showed that giving of bay leaf extract had no significant effect (P <0.05) on the observation variables. The conclusion of this study is the provision of bay leaf extract in drinking water up to the level of 12% has an impact on the percentage of gizzard and pancreas at the age of 6 weeks. At the age of 8 weeks no effect on the percentage of giblets and the percentage of digestive organs of mojosari alabio ducks. It is recommended to give bay leaves in the form of flour with a level higher than 12%. Keywords: bay leaf extract, mojosari alabio duck, giblet percentage, digestive organ percentage.